Combinaison des competences linguistiques dans l'utilisation de la nethode ado pour les lyceens : - Nguyễn, Thành Kia (Trường đại học Cần Thơ, 2010)
The aim of this work is to try to purpose nethodological operation in the hoping of improving the situation of current learning of high-school students in the province of Bentre.